Task and Distribution Sampling Affect Auditory Category Learning - Roark, Casey L. (Atten Percept Psychophys, 2018)
There is substantial evidence that two distinct learning systems are engaged in category learning. One is principally engaged when learning requires selective attention to a single dimension (rule-based) and the other is drawn online by categories requiring integration across two or more dimensions (information-integration). This distinction has been largely drawn from studies of visual categories learned via overt category decisions and explicit feedback. Recent research has extended this model to auditory categories, the nature of which introduces new questions for research. The current experiment addresses the influence of incidental versus overt training and category distribution sampling on learning information-integration and rule-based auditory categories. The results demonstrate that training task influences category learning, with overt feedback generally outperforming incidental feedback. Additionally, distribution sampling (probabilistic or deterministic) and category type (information-integration or rule-based) affects how well participants are able to learn. Specifically, rule-based categories are learned equivalently regardless of distribution sampling, whereas information-integration categories are learned better with deterministic sampling than probabilistic sampling. The interactions of distribution sampling, category type, and kind of feedback impacted category learning performance, but these interactions have not yet been integrated into existing category learning models. These results suggest new dimensions for understanding category learning, inspired by real-world properties of auditory categories.